2019
DOI: 10.4149/neo_2018_180820n633
|View full text |Cite
|
Sign up to set email alerts
|

Drug-resistance reversal in colorectal cancer cells by destruction of flotillins, the key lipid rafts proteins

Abstract: Multidrug resistance (MDR) of tumor cells attenuates the efficacy of anticancer drugs and has become the main reason for chemotherapy failure. It is indispensable to establish an effective way to reverse multidrug resistance. Our previous work has shown that downregulation of the ERK/MAPK signaling pathway activity can reverse the drug resistance of resistant cells. Furthermore, the effect of signal transduction is strongly associated with lipid rafts. The drug resistance is reversed successfully after lipid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…In particular, a recent study related a high expression of flotillin-2 to the incidence of lymph node metastasis and TNM stage in intrahepatic cholangiocarcinoma cell lines (Xu et al, 2020), as also previously observed in a variety of human solid tumors (Liu et al, 2017). High expression of flotillins was also observed in drug-resistant strains of colorectal cancer cells (Ye et al, 2019). Data from Ye and coworkers clearly demonstrated that flotillin silencing using lentivirus-mediated RNAi approach, by inducing destruction of lipid rafts, inhibited the drug resistance of the colorectal cancer cell line HCT-15 (Ye et al, 2019).…”
Section: Raft-associated Cholesterol Involvement In Migration Invasimentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, a recent study related a high expression of flotillin-2 to the incidence of lymph node metastasis and TNM stage in intrahepatic cholangiocarcinoma cell lines (Xu et al, 2020), as also previously observed in a variety of human solid tumors (Liu et al, 2017). High expression of flotillins was also observed in drug-resistant strains of colorectal cancer cells (Ye et al, 2019). Data from Ye and coworkers clearly demonstrated that flotillin silencing using lentivirus-mediated RNAi approach, by inducing destruction of lipid rafts, inhibited the drug resistance of the colorectal cancer cell line HCT-15 (Ye et al, 2019).…”
Section: Raft-associated Cholesterol Involvement In Migration Invasimentioning
confidence: 98%
“…High expression of flotillins was also observed in drug-resistant strains of colorectal cancer cells (Ye et al, 2019). Data from Ye and coworkers clearly demonstrated that flotillin silencing using lentivirus-mediated RNAi approach, by inducing destruction of lipid rafts, inhibited the drug resistance of the colorectal cancer cell line HCT-15 (Ye et al, 2019).…”
Section: Raft-associated Cholesterol Involvement In Migration Invasimentioning
confidence: 98%
“…[ 20 , 21 ] Angiogenesis exists in the whole development courses and progression of malignant tumors and is closely related to tumor development, invasion and metastasis. [ 22 ] Moreover, it has been found that membrane rafts are strongly associated with various cancers such as LUAD, [ 23 ] breast cancer, [ 24 ] colorectal cancer, [ 25 ] and pancreatic cancer. [ 26 ] In short, all these theoretical results are consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, the new molecules, such as plant PIs, that are selective, effective, and accessible, remains a great challenge for anticancer therapies, and nature has always been an important source. In addition, the resistance of tumor cells to different treatments is the limiting factor of anticancer therapies [21].…”
Section: Cancermentioning
confidence: 99%
“…The anticancer effect of purified polypeptide PI from C. cajan seeds has been reported against A549 cell line human lung carcinoma [11]. Besides, it is well known that PI activity from natural and synthetic inhibitors has expressive tumoricidal effects and interfere in cancer progression [16,19,20,21,43].…”
Section: Effect Of C Cajan Extracts On Sk-mel-28 Cells and Their Secmentioning
confidence: 99%